2020
DOI: 10.24200/sci.2020.52677.2833
|View full text |Cite
|
Sign up to set email alerts
|

Applying SVSSI sampling scheme on np-chart to Decrease the Time of Detecting Shifts - Markov chain approach, and Monte Carlo simulation

Abstract: One of the main criteria for judging about the power of control charts is their ability in fast detection of deviations and shifts in the process. Average time to signal (ATS) or adjusted average time to signal (AATS) are among such criteria calculated under a certain state and assumption. Several studies have shown that using the idea of variable design for control charts, by separating their limits to the safe and the warning regions, can allow quick discovery of shifts and increase sensitivities to small ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As future research, it is suggested to investigate other monitoring charts reviewed by Thaga and Sivasamy [9] for similar models. Designing attribute control charts with different sampling schemes, similar to [59], can be extended under the integrated model. Uncertainty in the model can be treated using a robust optimization approach applied in [54] and [60].…”
Section: Discussionmentioning
confidence: 99%
“…As future research, it is suggested to investigate other monitoring charts reviewed by Thaga and Sivasamy [9] for similar models. Designing attribute control charts with different sampling schemes, similar to [59], can be extended under the integrated model. Uncertainty in the model can be treated using a robust optimization approach applied in [54] and [60].…”
Section: Discussionmentioning
confidence: 99%
“…In other papers such as [10][11][12][13][14][15][16][17][18][19], more proposals for improving the np control chart can be found.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, if a sample falls outside the control limits, the sample belongs to the out-of-control region and the process is considered to be out-of-control, where corrective action(s) should be taken to remove the assignable cause(s). Some of the recent studies on VSI charts were made by Haq [23], Khoo et al [24] and Shojaee et al [25].…”
Section: Introductionmentioning
confidence: 99%